Growth Performance of Tilapia Fed with Feed Containing Moringa Leaf Meal and Shrimp Meal - Suardi Laheng; Dwi Utami Putri; Ika Wahyuni Putri; Darmawati Darmawati; Farida Igirisa; Pina Pina (Journal of Aquaculture and Fish Health, 2022)
The research objective of this study was to determine the impact of feed enrichment using Moringa leaf meal and shrimp meal on the growth performance of Tilapia. The initial weight of experimental fish was 6.10 ± 0.55 g/ head. The treatments given were Treatment A (feed without Moringa leaf meal and shrimp meal), Treatment B (commercial feed + 20% shrimp flour), Treatment C (commercial feed + 10% Moringa leaf meal + 20% shrimp meal), and Treatment D (commercial feed + 20% Moringa leaf meal + 20% shrimp meal). In total, there were 4 treatments with 3 replications each. Fish rearing lasted for 40 days. The results showed that the treatments had no effect on amount of feed consumption, protein efficiency ratio, specific growth rate, feed efficiency, survival rate, coefficient of variation and hepatosomatic index (p>0,05), but had an effect on the amount of protein consumption and body protein (p<0, 05). In conclusion, the enrichment of feed containing Moringa leaf meal and shrimp meal had no effect on the growth performance of Tilapia.